Two rare Cr–Ln (Ln = Dy, Tb) heterometallic cluster substituted polyoxometalates featuring hexameric aggregates: hydrothermal syntheses, crystal structures and magnetic studies. (25th January 2019) - Gu, Ya-Nan; Yu, Hao; Lin, Li-Dan; Wu, Yan-Lan; Li, Zhong; Pan, Wen-Yue; He, Jiang; Chen, Ling; Li, Qi; Li, Xin-Xiong
Abstract : Two hexameric Cr–Ln cluster substituted POMs have been obtained under hydrothermal conditions. They represent the first examples of 3d–4f heterometallic cluster substituted POMs incorporating Cr–Ln clusters. Abstract : Two hexameric chromium–lanthanide heterometallic cluster substituted polyoxometalates (POMs), K9 Na14 Cs12 H[Cr6 Dy6 (H2 O)12 (α-GeW10 O38 )6 ]·33H2 O (1-Dy ) and K9 Na14 Cs12 H[Cr6 Tb6 (H2 O)12 (α-GeW10 O38 )6 ]·65H2 O (1-Tb ), have been hydrothermally synthesized and structurally characterized through single-crystal X-ray diffraction analysis, powder X-ray diffraction analysis, thermogravimetric analysis, infrared spectroscopy and solid-state ultraviolet-visible spectroscopy. Compounds1-Dy and1-Tb represent the first examples of 3d–4f heterometallic cluster substituted POMs incorporating chromium–lanthanide clusters. What's more, magnetic investigations indicate that overall antiferromagnetic coupling is present in1-Dy and1-Tb .